Pengaruh Perendaman Infused Water dan Penyikatan Gigi Terhadap Kekasaran Permukaan Semen Ionomer Kaca Modifikasi Resin - Adrianing Chandra Kurniawati; Rosalina Tjandrawinata (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2014)
Resin modified glass ionomer cements (RMGIC) is a restorative dental material developed in 1967. The surface roughness of this restorative materials cause plaque accumulation which lead to quality degradation and brittleness of restoration. The aim of this research is to determine the effect of infused water immersion with brushing against the surface roughness changes of RMGIC. Forty samples (6mm diameter, 4mm thickness) were divided into 4 groups: group A light-cured RMGIC and group B self-cured RMGIC were soaked in 100mL of mineral water for 15 days, group C light-cured RMGIC and group D self-cured RMGIC were soaked in 100Ml infused water for 5 minutes and replaced by mineral water for 5 minutes repeated 20 times each day in 15 days. The samples were brushed for 2 minutes before and after immersion. Samples roughness were tested before and after treatment using a surface roughness tester. The surface roughness of group A was 1,28±0,49µm (before) 3.24±1.18µm (after), group B 0.52±0.23µm (before) 2.76±0.55µm (after), group C 1.87±0.45µm (before) 4.26±2.36µm (after), and group D 0.88±0.53µm (before) 4.01±1.09µm (after). Statistical analytics using t-test showed a significant difference in surface roughness value between before and after treatment, but no significant difference in the increase value of roughness after soaked in infused water between self-curing and light-curing RMGIC.